A new switched‐capacitor/switched‐inductor–based converter with high voltage gain and low voltage stress on switches. (21st February 2019) - Chavoshipour Heris, Pedram; Saadatizadeh, Zahra; Sabahi, Mehran; Babaei, Ebrahim
Summary: In this paper, a nonisolated transformerless switched‐capacitor/switched‐inductor–based dc‐dc converter with high voltage gain is proposed. The proposed converter has low voltage stress on switches and diodes which leads to decrease the switching losses. The voltage gain of the proposed converter can be increased by adding more diode‐capacitor modules at output side; therefore, the proposed converter has expandable structure. The proposed converter has higher voltage gain and lower voltage stress on switches comparing with the other similar switched‐capacitor–based converters. The proposed converter uses two switches with the same switching pattern. Therefore, its switching pattern is not complicated. In this paper, the proposed converter is analyzed during a switching period which has two operating modes. Moreover, the average current through the switches, diodes, and inductors; voltage stress on switches and diodes; voltage gain; maximum and minimum current of switches and diodes; and the efficiency curve are calculated. Finally, in order to verify the accuracy performance of the proposed converter, a 530‐W 40 to 920‐V prototype is implemented practically. Abstract : In this paper, a nonisolated transformerless switched‐capacitor/switched‐inductor–based dc‐dc converter with high voltage gain is proposed. The proposed converter has low voltage stress on switches and diodes which leads to decrease the switching losses. The voltage gain of the proposed converter can be increased by adding more diode‐capacitor modules at output side; therefore, the proposed converter has expandable structure. In order to verify the accuracy performance of the proposed converter, a 530‐W 40 to 920‐V prototype is implemented practically.